2021
DOI: 10.1186/s13014-021-01749-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous integrated boost concepts in definitive radiation therapy for esophageal cancer: outcomes and toxicity

Abstract: Background Radiation therapy and chemoradiation therapy play a major role in the definitive management of esophageal cancer. Survival in esophageal cancer patients is still relatively poor, mostly due to high rates of local recurrence and distant metastases. It is hypothesized that dose escalation in radiotherapy could improve outcomes. Therefore, this retrospective analysis aimed to investigate the outcomes and toxicity in patients treated with local dose escalation by means of using simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The 1-year and 3-year OS rates in our study were 75.2% and 40.2%, respectively, which were substantially higher than those reported by Ristau et al (63.9% and 37.6% respectively). 8 This result is in line with the findings of Xu et al, 9 but considerably lower than the 3- and 5-year survival rates of 53% and 44% and the median survival time of 43.2 months with IMRT reported by Lin et al 10 A possible explanation for this difference is that only 76.5% of the patients received CCRT in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The 1-year and 3-year OS rates in our study were 75.2% and 40.2%, respectively, which were substantially higher than those reported by Ristau et al (63.9% and 37.6% respectively). 8 This result is in line with the findings of Xu et al, 9 but considerably lower than the 3- and 5-year survival rates of 53% and 44% and the median survival time of 43.2 months with IMRT reported by Lin et al 10 A possible explanation for this difference is that only 76.5% of the patients received CCRT in our study.…”
Section: Discussionsupporting
confidence: 92%
“…J. Ristau et al, (2021) [20] announced 72.3 % of grade 3 acute toxicity, whereas only 47.5 % of cases were manageable; concomitant chemotherapy had to be interrupted or terminated in 19.8 %. Obviously, intolerable toxicity may worsen the patient's performance status and reduce the number of candidates for scheduled surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded IMRT use in definitive CRT/RT is safe and feasible, with acceptable survival rates and moderate toxicity. Prospective studies are needed [ 40 ].…”
Section: Radiation Therapy Approachmentioning
confidence: 99%